Association between 25(OH)D levels and clinical outcomes in patients infected with SARS-CoV-2: a cross-sectional study - Aleksandra Starosz; Anna Parfieniuk-Kowerda; Diana Martonik; Anna Moniuszko-Malinowska; Sławomir Pancewicz; Robert Flisiak; Marcin Moniuszko; Kamil Grubczak (Scientific Reports)
Abstract SARS-CoV-2 is an RNA virus that caused one of the most significant pandemics in the modern world. Although vaccination and treatment options have advanced, understanding host-related factors influencing disease severity remains critical, especially in the context of emerging variants and long-term complications. Since the beginning, numerous research studies have been conducted to better understand the mechanisms contributing to the severe onset of SARS-CoV-2 infection. Immunomodulatory properties of vitamin D are known for their positive impact on multiple conditions. Nevertheless, clinical trials suggested that vitamin D deficiency did not have as substantial a role as expected in conditions including asthma, cardiovascular or autoimmune diseases, and cancer. Moreover, low vitamin D levels could result from the ongoing inflammatory process. In this cross-sectional study, we assessed the level of 25-hydroxyvitamin D in hospitalized SARS-CoV-2-infected patients using immunoenzymatic tests (ELISA). Furthermore, the expression of the ORF1ab gene was detected, and the obtained results were correlated with laboratory parameters to establish their potential impact on the course of the disease. Severe 25(OH)D deficiency was found in subjects with active SARS-CoV-2 infection. We showed a significant relationship between 25(OH)D and extended hospitalization time. No link was demonstrated between vitamin D levels and clinical manifestations. Lower 25(OH)D values were associated with lower values of leukocytes, neutrophils and ferritin. In summary, our findings highlight the relevance of vitamin D status as a potential modulator of immune response and disease course in SARS-CoV-2 infection, underscoring the importance of continued investigation into host nutritional and inflammatory profiles during COVID-19.